2013
DOI: 10.1016/j.livsci.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of equations to predict body composition in Nellore bulls

Abstract: a b s t r a c tThe equations developed by Hankins and Howe (1946, HH), Marcondes et al. (2010, M10), Marcondes et al. (in press, M11) and Valadares Filho et al. (2006, V6) were evaluated to predict the body composition from the 9-10-11th rib cut in Nellore bulls. The evaluated equations estimated the physical and the carcass chemical composition, the empty body chemical composition and the noncarcass chemical composition. Thirty-seven Nellore bulls (1471 months old initially) with shrunk body weight of 25972… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A preliminary analysis had indicated that when the carcass fat and carcass protein are expressed as concentrations (Al-Jammas, Vernet, Agabriel, and Ortigues-Marty, 2014), the residuals of the models were significantly correlated with carcass weight (results not shown). A mass unit had also been recommended by Costa et al (2013) to compare data from different breeds, ages and weights at slaughter and by Charles and Johnson (1976) to account for the large between-breed differences in carcass composition at a similar carcass weight. As a result, HCW was systematically included in the models as an independent variable.…”
Section: Selection Of Units and Of The Statistical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary analysis had indicated that when the carcass fat and carcass protein are expressed as concentrations (Al-Jammas, Vernet, Agabriel, and Ortigues-Marty, 2014), the residuals of the models were significantly correlated with carcass weight (results not shown). A mass unit had also been recommended by Costa et al (2013) to compare data from different breeds, ages and weights at slaughter and by Charles and Johnson (1976) to account for the large between-breed differences in carcass composition at a similar carcass weight. As a result, HCW was systematically included in the models as an independent variable.…”
Section: Selection Of Units and Of The Statistical Modelmentioning
confidence: 99%
“…Relationships were also derived between reference measurements and combinations of proxy traits of individual animal data (O'Mara et al, 1998). Those relationships were established under well-controlled but limited conditions, such as a given diet, breed (Costa, Valadares, Detmann, Marcondes, and Rotta, 2013) or a given sex ; consequently, they are not applicable to other conditions. Therefore, in isolation, these studies cannot test whether the relationships are robust across breeds (e.g., British vs Continental) and whether they are independent of the progress in genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used the equations developed for calves, whose fat deposition occurs later in heifers and in bulls. Because for this difference in the deposition of tissues between the genders, some studies have reported that these equations overestimate the amount of fat [ 4 , 9 ] and undervalue the amount of muscle [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data used to test the equations are shown in Table 3 and were evaluated in their absolute weight (kg), according to the recommendations of Costa e Silva et al [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation